Excitation of a Primordial Cold Asteroid Belt as an Outcome of Planetary Instability - Deienno, Rogerio; Izidoro, Andre [UNESP]; Morbidelli, Alessandro; Gomes, Rodney S.; Nesvorny, David; Raymond, Sean N. (Iop Publishing Ltd, 2018)
The main asteroid belt (MB) is low in mass but dynamically excited. Here we propose a new mechanism to excite the MB during the giant planet (the Nice model) instability, which is expected to feature repeated close encounters between Jupiter and one or more ice giants (jumping Jupiter or JJ). We show that, when Jupiter temporarily reaches a high-enough level of excitation, both in eccentricity and inclination, it induces strong forced vectors of eccentricity and inclination across the MB region. Because during the JJ instability Jupiter's orbit jumps around, the forced vectors keep changing both in magnitude and phase throughout the whole MB region. The entire cold primordial MB is thus excited as a natural outcome of the JJ instability. The level of such an excitation, however, is typically larger than the current orbital excitation observed in the MB. We show that the subsequent evolution of the solar system is capable of reshaping the resultant overexcited MB to its present-day orbital state, and that a strong mass depletion (similar to 90%) is associated with the JJ instability phase and its subsequent evolution throughout the age of the solar system.
Keywords: minor planets, asteroids: general; planets and satellites: dynamical evolution and stability